1 The effects of a netball specific preseason programme on athletic performance and injury reduction: a pilot study. (20th December 2017) - Taylor, L; Forrest, R; Yoder, H
Abstract : Netball is one of the most popular sports for adolescent females which requires strength, speed and power to perform jumping and agility-based movements. However with adolescent female players susceptible to lower limb injuries than their male counterparts, in particular ankle sprains and anterior cruciate ligament rupture, Netball injury statistics are continuing to rise. Therefore prevention strategies and programmes are of priority to reduce these injury rates. The purpose of this research was to pilot a progressive six week preseason Netball specific multi-intervention programme and determine the effects on athletic performance and injury prevention against a control group. One hundred and twelve female players with a mean age 15±1 y; height 1.7±0.1 m; weight 62.0±10.1 kg; BMI 21.9±3.2 kg/m² participated in this study. Initial strength measures of mean press ups 6.8±0.7 s vs 8.1±0.9 s; prone hold 41.7±3.8 s vs 59.1±5.7 s; side hold left 41.7±3.8 s vs 59.1±5.7 s and right 21.9±1.7 s vs 44.0±3.7 s, case vs control respectively. Countermovement jump right 29.0±0.5 cm vs 28.6±0.4 cm; left 28.9±0.5 cm vs 26.3±0.8 cm and broad jump 181.3±2.2 cm vs 169.0±3.2 cm indicated this age group was below Netball NZ standards; with Illinois agility 18.6±0.1 s vs 19.4±0.2 s. Functional movement screen (FMS) scores case 10.9±0.3 vs control 9.8±0.2 indicated both groups high injury risk (FMS <14). Statistically significant improvements in Illinois agility (p<0.001) were recorded in both groups with increases in press ups (mean change 7.1±0.7 vs 2.53±1.2, p=0.004, d=0.8); side hold left (23.8±2.5 vs 13.6±1.2, p=0.001; d=0.9; right 24.4±2.7 vs 0.8±6.8, p=0.001; d=0.9) compared to the control. Both groups improved in FMS scores (p<0.02) however only those involved with the preseason programme achieved results indicating a reduction in injury risk (16.6±1.6 vs 11.7±2.6; p<0.001; d=1.6). Predominant injuries during the netball season were contact ankle injuries with no differences in incidence. Three serious knee injuries were sustained during the Netball season, two in the control group and one in the intervention group. There is evidence to suggest that preseason Netball specific programme can improve athlete performance and may decrease the risk of serious knee injury.